Nibelung Adaptations in Right-wing Extremism - Georg Schuppener (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This study examines the forms in which references to the Nibelungenlied can be found in the right-wing extremist scene because right-wing extremists in Germanspeaking countries frequently hijack cultural history for their own purposes. This evaluation focuses on far-right Internet domains. Here, references are primarily found in three areas of right-wing extremist life: martial arts, clothing, and music. In addition, there are several isolated references to the Nibelungen. The right-wing extremist adaptation of the Nibelungen material focuses primarily on the two characters: Siegfried and Hagen. Other characters from the Nibelungenlied play no part in rightwing extremist appropriation. In addition to the name references, (small) portions of the Nibelungenlied’s content are manipulated, particularly in songs performed by various right-wing extremist bands. The aspects of war and battle are emphasized, with special attention and appreciation given to the Nibelungs’ alleged loyalty. All approaches to the Nibelungen are instrumentalized in the right-wing extremist worldview to propagate social Darwinist ideas of survival of the fittest as well as to shape right-wing extremist identities. All in all, it becomes clear that the emphasis is on a superficial and violence-focused appropriation rather than an in-depth examination of the medieval work. This bears striking similarities to the reception and instrumentalization of Nordic-Germanic mythology in the right-wing extremist movement.